Zauj and Imara'ah in The Qur'an, Says Mutaradif (A Pre-Emptive Study of the Quran's Semantic Interpretation by Toshihiko Izutsu) - Aini, Sabilla Qurratu; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2023)
The terms lafadz, which means